2006
DOI: 10.1002/pros.20453
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic comparison of prostate cancer cell lines LNCaP-FGC and LNCaP-r reveals heatshock protein 60 as a marker for prostate malignancy

Abstract: The LNCaP-FGC/LNCaP-r model, characterized by 2-D electrophoresis, reveals distinct proteomic alterations. With HSP60, results from cell-lines correlated with clinical results, indicating that this model can be used for dissection of mechanisms involved in transformation to androgen resistance and assignment of protein markers in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…As such, the chaperonin has become the subject of studies aiming at determining its precise role as etiologic-pathogenic factor and also aiming at inventing new diagnostic and therapeutic ways centered on it. Adrenal gland Adrenal Cushing's tumor [168] Bladder Transitional cell carcinoma; carcinosarcoma [169][170][171] Bone marrow, blood, lymph nodes Acute myeloid leukemia; Hodgkin's lymphoma [155,[172][173][174] Brain Astroglyoma; glioblastoma; meningioma [175][176][177][178][179] Breast Breast ductal carcinoma [180,181] Esophagus Oesophageal carcinoma [182,183] Large bowel Adenocarcinoma [23,169,[184][185][186][187] Liver Hepatocellular carcinoma [188] Lung Bronchial carcinoma [25,26,189,190] Ovary Serous ovarian cancer [191] Prostate Prostate carcinoma [24,[192][193][194] Stomach Gastric maltoma [195] Uterus Exocervical carcinoma [22,196] Adapted from [2]. ATP synthase [197] Dihydrofolatereductase [37,46] Hsp10 [37,41] Human Carbonicanhydrase II [37,198,…”
Section: Expert Opinionmentioning
confidence: 99%
“…As such, the chaperonin has become the subject of studies aiming at determining its precise role as etiologic-pathogenic factor and also aiming at inventing new diagnostic and therapeutic ways centered on it. Adrenal gland Adrenal Cushing's tumor [168] Bladder Transitional cell carcinoma; carcinosarcoma [169][170][171] Bone marrow, blood, lymph nodes Acute myeloid leukemia; Hodgkin's lymphoma [155,[172][173][174] Brain Astroglyoma; glioblastoma; meningioma [175][176][177][178][179] Breast Breast ductal carcinoma [180,181] Esophagus Oesophageal carcinoma [182,183] Large bowel Adenocarcinoma [23,169,[184][185][186][187] Liver Hepatocellular carcinoma [188] Lung Bronchial carcinoma [25,26,189,190] Ovary Serous ovarian cancer [191] Prostate Prostate carcinoma [24,[192][193][194] Stomach Gastric maltoma [195] Uterus Exocervical carcinoma [22,196] Adapted from [2]. ATP synthase [197] Dihydrofolatereductase [37,46] Hsp10 [37,41] Human Carbonicanhydrase II [37,198,…”
Section: Expert Opinionmentioning
confidence: 99%
“…Proteins have been separated by 2D-PAGE, and differentially expressed proteins subsequently identified. Of these, HSP60 (60 kDa heat shock protein) was more abundant in LNCaP-r than LNCaP-FGC cells, showing a correlation with the resistant phenotype (80). Immunohistochemistry studies on prostate tissues demonstrated that prostate epithelial cells showed a moderate to strong HSP60 staining, without any apparent correlation between Gleason grade and staining intensity.…”
Section: Tissue Proteomic-based Molecular Analysis Of Prostate Cancermentioning
confidence: 98%
“…Comparative proteomic studies using 2-D gel electrophoresis coupled to mass spectrometric identification has been applied in studies of various cancers, including hepatomas [4] , lung cancer [5] , prostate [6] , and ovarian cancers [7] . The search for markers and vaccines at the protein level is more reliable than at the transcriptional level, as the translation process is often unpredictable and the spatiotemporal in situ localization of a given protein is not often correlated with its in situ expression pattern [8] .…”
Section: Introductionmentioning
confidence: 99%